Effects of freshwater salinization on a salt‐naïve planktonic eukaryote community. Issue 1 (8th February 2022) - Astorg, Louis; Gagnon, Jean‐Christophe; Lazar, Cassandre S.; Derry, Alison M.
Abstract: Freshwater salinization is a widespread issue, but evidence of ecological effects on aquatic communities remains scarce. We experimentally exposed salt‐naive plankton communities of a north‐temperate, freshwater lake to a gradient of chloride (Cl − ) concentration (0.27–1400 mg Cl L −1 ) with in situ mesocosms. Following 6 weeks, we measured changes in the diversity, composition, and abundance of eukaryotic 18S rRNA gene. Total phytoplankton biomass remained unchanged, but we observed a shift in dominant phytoplankton groups with increasing salt concentration, from Cryptophyta and Chlorophyta at lower chloride concentrations (< 185 mg Cl − L −1 ) to Ochrophyta at higher chloride concentrations (> 185 mg Cl − L −1 ). Crustacean zooplankton and rotifers were sensitive to the salinity, and disappeared at low chloride concentrations (< 40 mg Cl − L −1 ). While ciliates thrived at low chloride concentrations (< 185 mg Cl − L −1 ), fungal groups dominated at intermediate chloride concentrations (185–640 mg Cl − L −1 ), and only phytoplankton remained at the highest chloride concentrations (> 640 mg Cl − L −1 ).